Inborn errors of purine metabolism: clinical update and therapies. Issue 5 (28th June 2014) - Balasubramaniam, Shanti; Duley, John A.; Christodoulou, John
Abstract: Inborn errors of purine metabolism exhibit broad neurological, immunological, haematological and renal manifestations. Limited awareness of the phenotypic spectrum, the recent descriptions of newer disorders and considerable genetic heterogeneity, have contributed to long diagnostic odysseys for affected individuals. These enzymes are widely but not ubiquitously distributed in human tissues and are crucial for synthesis of essential nucleotides, such as ATP, which form the basis of DNA and RNA, oxidative phosphorylation, signal transduction and a range of molecular synthetic processes. Depletion of nucleotides or accumulation of toxic intermediates contributes to the pathogenesis of these disorders. Maintenance of cellular nucleotides depends on the three aspects of metabolism of purines (and related pyrimidines): de novo synthesis, catabolism and recycling of these metabolites. At present, treatments for the clinically significant defects of the purine pathway are restricted: purine 5′‐nucleotidase deficiency with uridine; familial juvenile hyperuricaemic nephropathy (FJHN), adenine phosphoribosyl transferase (APRT) deficiency, hypoxanthine phosphoribosyl transferase (HPRT) deficiency and phosphoribosyl‐pyrophosphate synthetase superactivity (PRPS) with allopurinol; adenosine deaminase (ADA) and purine nucleoside phosphorylase (PNP) deficiencies have been treated by bone marrow transplantation (BMT), and ADA deficiency with enzyme replacement with polyethylene glycol (PEG)‐ADA, or erythrocyte‐encapsulated ADA; myeloadenylate deaminase (MADA) and adenylosuccinate lyase (ADSL) deficiencies have had trials of oral ribose; PRPS, HPRT and adenosine kinase (ADK) deficiencies with S‐adenosylmethionine; and molybdenum cofactor deficiency of complementation group A (MOCODA) with cyclic pyranopterin monophosphate (cPMP). In this review we describe the known inborn errors of purine metabolism, their phenotypic presentations, established diagnostic methodology and recognised treatment options.